Web-Based Student Violation Monitoring Information System Design at SMK Gandasari - Jully Triansyah; Maya Apriyanti; Rusma Insan Nurachim; Sandra Dewi Saraswati (The IJICS (International Journal of Informatics and Computer Science), 2022)
SMK Gandasari is one of the vocational high schools in Tangerang City. The purpose of the school authority is to improve student discipline related to increasing student discipline at school, namely by attendance in class or in attendance calls. Parents are still very concerned about the condition of the children at school, whether they really behave well or not, and parents cannot do direct monitoring but have to wait when the report cards are distributed. In monitoring violations, Gandasari Vocational School students still use paper media, namely by being recorded in a book, this makes information about student behavior slow to reach parents. To overcome this, a student monitoring information system is needed at the Gandasari Vocational School to communicate information to parents of students that are directly related to the condition of their students at school through computerized data processing using a web-based system. To analyze the problem data and the needs of a student monitoring information system using the waterfall method, with stages of needs analysis, design, code generation, system design with Unified Modeling Language (UML) Diagrams, programs and testing. The waterfall method has the main stages of the waterfall model that reflect basic development activities. There are 5 (five) stages in the Waterfall method, namely requirements analysis and definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. The result of this research is a website for student violation information systems as a solution to existing problems